Methodology of ECG Interpretation in the Lyon Program - Arnaud, P.; Rubel, P.; Morlet, D.; Fayn, J.; Forlini, M.C. (Methods of Information in Medicine, 1990)
To provide an in-depth interpretation of the spatial QRS-T contour, we established a set of vectorcardiographic parameters computed octant by octant. For each statement the criteria constitute a model which is closely related to pathophysiological patterns. The diagnostic strategy is of the heuristic type. For each diagnosis a table lists several criteria providing both specific and differential diagnostic information. Inter-table competition is handled by specific logic. The program classifies diagnoses according to the number of non-satisfied criteria. Three versions are available including 124,51 and 7 diagnoses, respectively. The first, intended for interpretation of complex situations, has given satisfactory results in such situations. Rhythm analysis is performed from 8-second recordings.All functions - acquisition, quality control, choice of a dominant complex, wave recognition, parameter extraction, interpretation, editing, storage -are integrated into a mobile cart. A complementary program performs serial analysis of successive tracings. It highlights with great precision morphological changes in the spatial loops and interval variations.
Keywords: Computerized ECG Analysis; Serial ECG Analysis; ECG Signal Processing; Vectorcardiography; Expert Systems